Disaster studies. (September 2013) - Lindell, Michael K
Disaster studies address the social and behavioral aspects of sudden onset collective stress situations typically referred to as mass emergencies or disasters. These situations can be created by natural hazards, technological accidents, violent intergroup conflicts, shortages of vital resources, and other major hazards to life, health, property, well-being, and everyday routines. Disaster studies address the impacts of these events on all social units ranging from individuals and households to nation-states. All aspects of the life history of such events, both actual and threatened, are examined in terms of the ways in which populations at risk conduct hazard and vulnerability analyses as well as plan and implement mitigation, preparedness, response, and recovery actions.